Self-healing hydrogels based on the Knoevenagel condensation reaction for wound healing - Xiaoya Ding; Yunru Yu; Yan Zu (Biomedical Technology, 2023)
Self-healing hydrogels are promising biomedical materials owing to their ability to restore the structure fracture and regain the initial functions. However, a comprehensive review of the dynamic hydrogels based on the Knoevenagel Condensation (KC) for wound healing is yet lacking. Here, we first summarize the recent advances in self-healing hydrogels constructed by the KC reaction, and then systematically illustrate the reaction process and self-healing mechanisms. The features of these hydrogels, for instance, self-healing characteristics, injectability, thermosensitivity, as well as thermoplastic properties are also highlighted. In addition, a series of hydrogels constructed by this reaction in the presence of various catalysts are presented and discussed. Furthermore, the potential application within the rapidly expanding field of wound healing is discussed in detail. Finally, recommendations to guide the designing strategies and a perspective on challenges faced by this kind of hydrogels are also described.